Immobilization of Saccharomyces cerevisiae for application in paper-based microfluidic fuel cell. (12th February 2023) - García-Villagómez, A.D.; Galindo-de-la-Rosa, J.; Dector, A.; Álvarez, A.; Rodríguez-Morales, J.A.; Olivares-Ramírez, J.M.; Arjona, N.; Chávez-Ramírez, A.U.; Vallejo-Becerra, V.
Abstract: Microfluidic fuel cells that use microorganisms to oxidize different organic substances to generate electricity are gaining importance due to their versatility to use different fuels. Saccharomyces cerevisiae has used for various purposes due to its capacity to ferment broad spectrum of carbohydrates. In this research, the development of bioanodes based on the immobilization of this yeast was carried out to apply them in the evaluation of a paper lateral-flow microfluidic fuel cell. Immobilization was performed using two different supports, Vulcan carbon and graphene oxide, and four carbohydrates as fuel (saccharose, glucose, fructose, and maltose). The results indicated that the yeast is better distributed and reaches a higher capacity to oxidize carbohydrates when is immobilized on graphene oxide, this bioanode shows better performance in the microfluidic device, reaching a potential above 0.9V when saccharose are used as fuel, representing a promising approach to use microbial bioanodes in small energy conversion devices. Highlights: Electrodes based on the Saccharomyces cerevisiae immobilization were used to make paper lateral-flow microfluidic fuel cells. Immobilization was performed using Vulcan carbon (VC) and graphene oxide (GO) as supports. Saccharose, glucose, fructose, and maltose were used as fuel in the microfluidic device. The GO-based bioanode shows better performance, reaching a potential greater than 0.9V when saccharose is supplied.